The Choice of the Iodinated Radiographic Contrast Media to Prevent Contrast-Induced Nephropathy. (15th October 2014) - Andreucci, Michele; Faga, Teresa; Pisani, Antonio; Sabbatini, Massimo; Russo, Domenico; Michael, Ashour
Abstract : In patients with preexisting renal impairment, particularly those who are diabetic, the iodinated radiographic contrast media may cause contrast-induced nephropathy (CIN) or contrast-induced acute kidney injury (CI-AKI), that is, an acute renal failure (ARF), usually nonoliguric and asymptomatic, occurring 24 to 72 hours after their intravascular injection in the absence of an alternative aetiology. Radiographic contrast media have different osmolalities and viscosities. They have also a different nephrotoxicity. In order to prevent CIN, the least nephrotoxic contrast media should be chosen, at the lowest dosage possible. Other prevention measures should include discontinuation of potentially nephrotoxic drugs, adequate hydration with i.v. infusion of either normal saline or bicarbonate solution, and eventually use of antioxidants, such as N-acetylcysteine, and statins.